O istotnym i nieistotnym występowaniu jakiegoś wyrażenia w innym wyrażeniu - Brożek, Anna (Filozofia Nauki, 2005)
Let us assume that the expression A is a segment of the expression B. Now, let us assume that we try to transform the expression B into the expression B', removing A from B or replacing A with another expression, say A'. When shall we say that A is irremovable or occurs in B essentially? We shall do it, if we can neither remove A from B nor replace A with A', not influencing upon important properties of B. On the other hand, when shall we say that the occurrence A in B is essential? We shall do it, if we can transform B into B' changing no <> properties of B. Let us say it more precisely. Let us assume - as concerns expressions x, y, x' and y' - that: (a) x occurs in y; (b) the only structural difference between y and y' is that x does not occur in y', or x' occurs in y instead of x. Then: x occurs in y inessentially-with-respect-to-w of y, iff y' is the same as y with respect to p. Correspondingly: x occurs in y essentially-with-respect-to-w of y, iff y' is different as y with respect to p. The occurrence x in y may be essential or inessential with respect to syntactic, semantic or pragmatic properties of y. In my paper, I discuss a variety of detailed concepts of the (in)essential occurrence of expressions in another expressions with respect to semantic properties of these expressions, i.e. with respect to semantic category, logical value, denotation and connotation. I also discuss some philosophical and methodological implications of presented solutions of the problem.